FRAILTY SYNDROME IN INSTITUTIONALIZED OLDER ADULTS: IS HYPERTENSION A PROTECTIVE FACTOR? - Marques, Maria Armanda (2022)
Introduction: Portuguese older adults have a high prevalence of chronic disease, such as hypertension. Frailty is a multidimensional syndrome, in which a state of extreme vulnerability to endogenous and exogenous factors is recognized, due to cumulative decline associated with the ageing process, potentially leading to a state of total dependence. The aim of this investigation was to establish na association between the presence of hypertension and frailty syndrome in institutionalized older adults. Methods: This is a cross-sectional study for which institutionalized older adults from two institutions in Leiria district (Portugal) were invited to participate. Demographic data was collected, as well as clinical history. Frailty syndrome was assessed using Fried’s Frailty Phenotype. This study was approved by the Ethical Committee of the Centro Académico de Medicina de Lisboa. All participants or legal representatives signed the informed written consent for participation. Results: One hundred and forty-seven older adults were included, mainly female (63,2%), with a mean age of 82.6 years old (SD=8.6), ranging from 63 to 103. Hypertension was found in 59.6% of the sample. Frailty syndrome was found in 41.5%. Simultaneously, frailty and hypertension were present in 59.6% of the sample. No statistically significant association was found between the presence of hypertension and frailty. Conclusion: In this study, institutionalized older adults presented a high prevalence of hypertension and frailty. The possible influence of the presence of frailty syndrome in the therapeutic benefit of treating hypertension highlights the importance of assessing this condition in individuals with hypertension.